Lithium battery structural member over-current capability test method, temperature rise prediction method and application of lithium battery structural member over-current capability test method and temperature rise prediction method
By integrating foil, adapter and busbar on the pole column of the lithium battery ceiling, combining ultrasonic and laser welding, using phase change heat transfer materials and thermocouples to monitor the temperature changes in the connection position of the lithium battery, the current solution is solved There are problems with low testing efficiency in the technology, and efficient overcurrent capability analysis and temperature rise prediction are achieved.
Patent Information
- Application Number
- CN202411182202.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art is difficult to efficiently monitor the overcurrent and thermal conductivity of the connection position of lithium batteries, especially under high current fast charging conditions, and the existing testing methods are inefficient and complex.
By integrating the foil, adapter sheet and busbar on the pole column of the top cover plate, a composite assembly is formed, and the connection is performed using ultrasonic welding and laser welding, combined with phase change heat transfer materials and thermocouples, constant current charging or discharge tests are performed. Monitor temperature changes to analyze overcurrent capabilities and establish a temperature rise prediction expression based on test results.
It can effectively monitor the temperature changes of structural parts without the need to assemble a complete battery, simplify the testing process, improve the testing efficiency, determine the weak points of the components, and provide a basis for temperature rise prediction for structural design.
Smart Images

Figure CN119125885A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery detection, and in particular to a method for testing the overcurrent capacity of a lithium battery structural component, a method for predicting a temperature rise, and applications thereof. Background Art
[0002] The poles of the adapter and the top cover are usually connected by laser welding, and the pole piece and the adapter are usually connected by ultrasonic welding. Under high-current fast charging, these connection locations are often weak points with high temperature rise. Therefore, in order to determine whether the connection can meet the requirements of current capacity and heat conduction capacity, the above locations need to be designed and monitored.
[0003] In the prior art, the heat generation of connection positions and structural parts such as adapters is mainly evaluated through simulation calculations, which is difficult to test in practice; or after the battery is assembled, it is monitored by arranging temperature sensing lines in advance, but this greatly reduces efficiency.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first purpose of the present invention is to provide a method for testing the current carrying capacity of lithium battery structural parts. By integrating the foil, adapter and busbar on the pole of the top cover plate, a simple composite component is obtained. The temperature changes of important positions of the structural parts can be monitored without assembling them into a complete battery, and the current carrying capacity of the structural parts can be analyzed. The method is simple and the test efficiency is high. By monitoring the temperature changes, the weak points of the components can also be determined.
[0006] The second purpose of the present invention is to provide a temperature rise prediction method, which can provide a basis for structural design by fitting the temperature rise prediction expression based on the test results obtained by the test method of the current capacity of lithium battery structural parts.
[0007] The third object of the present invention is to provide a method for testing the overcurrent capacity of a lithium battery structural component or a method for predicting temperature rise for use in the preparation of a lithium-ion battery.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] The present invention first provides a method for testing the overcurrent capacity of a lithium battery structural component, comprising the following steps:
[0010] A composite component is obtained; the composite component comprises a busbar, a top cover plate, an adapter plate and a foil material which are arranged in sequence; wherein one end of the adapter plate is connected to the foil material by ultrasonic welding to form a first welding position and a second welding position, and the foil material is arranged above the adapter plate; a phase change heat transfer material is arranged on the surface of the foil material; the other end of the adapter plate is connected to the pole of the top cover plate by laser welding to form a third welding position, and the top cover plate is arranged below the adapter plate; below the top cover plate, the busbar is connected to the pole of the top cover plate by laser welding.
[0011] The composite assembly is connected to a charge and discharge test cabinet and a thermocouple respectively, and then a constant current charge or constant current discharge test is performed.
[0012] Furthermore, the foil material includes aluminum foil or copper foil.
[0013] Furthermore, the cross-sectional area of the adapter sheet is ≥ 15 mm 2 .
[0014] Furthermore, the phase change heat transfer material includes a graphene thermal conductive film.
[0015] Furthermore, the connection method between the composite component and the charge and discharge test cabinet includes: using the busbar as the first test electrode and the foil as the second test electrode, connecting the first test electrode and the second test electrode to the first test end and the second test end of the charge and discharge test cabinet respectively; wherein the first test electrode and the first test end are bolted together through a through hole on the busbar; the second test end includes a clamping structure, and the second test electrode and the second test end are connected through the clamping structure; the clamping structure includes a low-impedance gold-plated copper material.
[0016] Furthermore, the connection method between the composite component and the thermocouple includes: arranging the thermocouple at the first welding position, the second welding position, the third welding position and the fourth temperature measuring point, and fixing them respectively; wherein the fourth temperature measuring point is the center of gravity within the plane formed by the first welding position, the second welding position and the third welding position; the fixing method includes: fixing by gluing with high temperature resistant insulating tape.
[0017] Furthermore, the cutoff condition of the constant current charging or constant current discharging is controlled by temperature rise or power-on time.
[0018] Furthermore, the test starting temperature of the constant current charge or constant current discharge is 25°C±2°C.
[0019] Furthermore, after the constant current charging or constant current discharging test is completed, a mechanical stability test is performed on the composite component; the mechanical stability test includes a tensile test.
[0020] The present invention further provides a temperature rise prediction method, comprising the following steps: performing a complete factorial analysis based on the test results obtained by the test method for the current capacity of the lithium battery structural component, establishing a multivariate linear regression fitting model of key factors and temperature rise, and calculating the temperature rise prediction value.
[0021] Furthermore, the key factors include at least one of current, time, cross-sectional area of the adapter and ultrasonic welding area.
[0022] Furthermore, in the process of complete factorial analysis, the P value of each factor in the fitting model is used to make a judgment and the effect factors with a P value greater than 0.05 are screened out.
[0023] The present invention also provides the application of the test method of the current carrying capacity of the lithium battery structural component or the temperature rise prediction method in the preparation of lithium ion batteries.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The present invention provides a method for testing the overcurrent capacity of a lithium battery structural component. By integrating the foil, the adapter, and the busbar on the pole of the top cover plate to obtain a simple composite assembly, the temperature change of important positions of the structural component can be monitored without assembling a complete battery. The method is simple and the test efficiency is high. By monitoring the surface temperature of different positions of the structural component under different currents, the overcurrent capacity of the structural component can be analyzed.
[0026] (2) The test method for the overcurrent capacity of lithium battery structural components provided by the present invention can determine the weak points of the components by monitoring temperature changes, and compare the actual test overcurrent time and temperature with the design values, so as to determine whether the design of the adapter area, welding area and tab size is qualified.
[0027] (3) The temperature rise prediction method provided by the present invention fits the temperature rise prediction expression according to the test results obtained by the test method of the current carrying capacity of the lithium battery structural parts, which can provide a basis for structural design. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 A partial front view of the composite assembly provided by the present invention;
[0030] Figure 2 A schematic diagram of the structure of the composite assembly provided by the present invention;
[0031] Figure 3 A schematic diagram of the connection between the composite assembly and the charge and discharge test cabinet provided by the present invention;
[0032] Figure 4 A physical diagram of the connection between the composite assembly and the charge and discharge test cabinet provided by the present invention;
[0033] Figure 5 This is the fitting result provided by the present invention. DETAILED DESCRIPTION
[0034] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0035] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0036] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0037] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0038] In a first aspect, the present invention provides a method for testing the current carrying capacity of a lithium battery structural component, comprising the following steps: first, obtaining a composite component. The composite component comprises a busbar, a top cover plate, a transfer sheet and a foil material stacked in sequence from bottom to top, see Figure 1 shown.
[0039] Specifically, Figure 1 and Figure 2 As shown, one end of the adapter sheet is connected to the middle position of the foil material by ultrasonic welding to form a first welding position and a second welding position, and the foil material is arranged above the adapter sheet. Furthermore, a phase change heat transfer material is arranged on one surface (top surface) of the foil material.
[0040] See also Figure 1 and Figure 2 The other end of the adapter (i.e., the end away from the first welding position and the second welding position) is connected to the pole of the top cover plate by laser welding to form a third welding position, and the top cover plate is arranged below the adapter.
[0041] It can be understood that the adapter sheet is arranged between the foil material and the top cover plate.
[0042] See also Figure 1 and Figure 2 The busbar is arranged below the top cover plate, and the busbar is connected to the pole of the top cover plate by laser welding.
[0043] Afterwards, the composite assembly is connected to a charge and discharge test cabinet and a thermocouple respectively, and then a constant current charge or constant current discharge test is performed, and the data is recorded.
[0044] The present invention provides a method for testing the current carrying capacity of a lithium battery structural component. By integrating a foil, an adapter, and a busbar on a pole of a top cover plate, a simple composite assembly is obtained. The temperature change of important positions of the structural component can be monitored without assembling a complete battery. The method is simple and has high testing efficiency.
[0045] By monitoring the surface temperature of different locations of the structural parts under different currents, the current carrying capacity of the structural parts can be analyzed.
[0046] At the same time, by monitoring temperature changes, the weak points of the components can be determined, and the actual tested overcurrent time and temperature can be compared with the design values to determine whether the designs of the adapter area, welding area and tab size are qualified.
[0047] In some specific implementations, the foil material includes aluminum foil or copper foil.
[0048] In some specific embodiments, the cross-sectional area of the adapter sheet is ≥ 15 mm 2 , including but not limited to 15mm 2 、16mm 2 、17mm 2 、18mm 2 、19mm 2 , 20mm 2 、23mm 2 , 25mm 2 、28mm 2 , 30mm 2 、33mm 2 、35mm 2 、38mm 2 , 40mm 2 , 45mm 2 , 50mm 2 The larger the cross-sectional area, the stronger the battery overcurrent capacity. The effect of setting different cross-sectional areas on the battery overcurrent capacity can be compared.
[0049] In some specific embodiments, the ultrasonic welding areas of the first welding position and the second welding position formed by ultrasonic welding of the adapter sheet and the foil are independently 50 to 150 mm 2 , including but not limited to 50mm 2 、60mm 2 , 80mm 2 , 100mm 2 , 120mm 2 、130mm 2 、150mm 2 Any point value in or any range of values between them.
[0050] In some specific embodiments, the phase change heat transfer material includes a graphene thermal conductive film. That is, the phase change heat transfer material is composed of graphene, which has a thermal conductivity. Considering the heat dissipation factor of the battery, graphene is introduced as a heat dissipation material to simulate actual working conditions.
[0051] In some specific embodiments, the size of the graphene thermally conductive film is close to or equal to that of the foil, that is, the area of the graphene thermally conductive film is preferably approximately equal to the area of the foil, or the top surface of the foil is completely covered with the graphene thermally conductive film to simulate the actual heat transfer condition of the battery cell.
[0052] In some specific embodiments, the method for connecting the composite assembly and the charge and discharge test cabinet includes: Figure 3 and Figure 4As shown, the busbar is used as a first test electrode, the foil is used as a second test electrode, and the first test electrode and the second test electrode are connected to a first test end and a second test end of a charge and discharge test cabinet respectively.
[0053] In some specific implementations, see Figure 3 and Figure 4 As shown, the first test electrode and the first test end are bolted together through a through hole on the busbar.
[0054] As an example, the through hole on the busbar may be a circular hole with a diameter of 9 mm, see Figure 2 As shown, but not limited to.
[0055] In some specific implementations, see Figure 3 and Figure 4 As shown, the second test end includes a clamping structure, and the second test electrode and the second test end are connected through the clamping structure to conduct current.
[0056] In some specific embodiments, the clamping structure includes a low-impedance gold-plated copper material. Specifically, the contact position between the clamping structure and the second test electrode is a low-impedance gold-plated copper material. This can reduce contact impedance and heat generation, thereby reducing external influencing factors.
[0057] In some specific embodiments, the method for connecting the composite component and the thermocouple includes: arranging the thermocouple at the first welding position, the second welding position, the third welding position and the fourth temperature measuring point, and fixing them, so as to determine the weak point where the temperature rise is higher when the current flows. Figure 2 The solid square black dots in the figure are the arrangement points of the thermocouples.
[0058] In some specific implementations, the fourth temperature measurement point is the center of gravity of the plane formed by the center of gravity of the first welding position, the center of gravity of the second welding position and the center of gravity of the third welding position, see Figure 2 shown.
[0059] In some specific implementations, the fixing method includes: fixing with high temperature resistant insulating tape.
[0060] In some specific implementations, the cutoff condition of the constant current charging or constant current discharging is controlled by temperature rise or power-on time.
[0061] In some specific embodiments, the test starting temperature of the constant current charge or constant current discharge is 25°C±2°C, such as 23°C, 24°C, 25°C, 26°C or 27°C.
[0062] In some specific implementations, after the constant current charge or constant current discharge test is completed, a mechanical stability test is performed on the weak position of the composite component, and the test results are recorded; wherein the mechanical stability test includes a tensile test. The tensile test can evaluate the welding reliability, that is, evaluate the welding reliability of the weak position after the current is applied.
[0063] In some specific implementations, the tensile test is performed using a Kexun universal tensile testing machine.
[0064] In the second aspect, the present invention provides a temperature rise prediction method, or a method for obtaining a temperature rise prediction expression, comprising the following steps: performing a complete factorial analysis based on the test results obtained by the test method for the current capacity of the lithium battery structural parts, establishing a multivariate linear regression fitting model of key factors and temperature rise, and calculating the temperature rise prediction value.
[0065] The present invention fits the temperature rise prediction expression according to the test results obtained by the test method of the current carrying capacity of the lithium battery structural component, which can provide a basis for structural design.
[0066] In some specific implementations, the key factor includes at least one of current, time, a cross-sectional area of the adapter, and an ultrasonic welding area.
[0067] In some specific embodiments, the collected data points, such as current (I / A), time (t / s), cross-sectional area of the adapter (S1 / mm 2 ) and ultrasonic welding area (S2 / mm 2 )The key factors are completely factored out, and a multivariate linear regression fitting model of key factors and temperature rise is established to calculate the predicted value of temperature rise. Among them, the cross-sectional area of the adapter refers to the product of the width and thickness of the adapter. The ultra-transverse wave welding area refers to the product of the length and width of the ultrasonic welding head.
[0068] In some specific implementations, during the complete factorial analysis, a judgment is made based on the P value of each factor in the fitting model and the effect factors with a P value greater than 0.05 are screened out.
[0069] Effect factors with a P value greater than 0.05 do not contribute significantly to the model. After removing these effects, the model is refitted to obtain more accurate estimates of the model parameters related to the active effects in order to achieve the purpose of simplifying the model.
[0070] In a third aspect, the present invention provides the application of the test method for the current carrying capacity of the lithium battery structural component or the temperature rise prediction method in the preparation of lithium-ion batteries.
[0071] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0072] Example 1
[0073] The method for testing the overcurrent capability of a lithium battery structural component provided in this embodiment includes the following steps:
[0074] (1) Prepare a composite assembly including busbar, top cover, adapter and foil: Cut the foil according to the design size. In this embodiment, a single layer of aluminum foil with a thickness of 12 μm is used. The width of the aluminum foil is 40 mm and the number of layers is 64. The surface of the foil has a graphene thermal conductive film. The foil is connected to the 19.50 mm by ultrasonic welding. 2 、30.75mm 2 、40.00mm 2 The first welding position and the second welding position are formed on the adapter sheet with a cross-sectional area of 50 mm (64 layers of single aluminum foil are welded on the adapter sheet by ultrasonic welding), and the ultrasonic welding area is 50 mm 2 , 100mm 2 , 150mm 2 Then the adapter with foil is connected to the bottom of the pole of the top cover plate by laser welding to form the third welding position (the adapter is located between the foil and the top cover plate). The laser welding area is 120mm 2 Finally, the busbar is connected to the top of the pole of the top cover plate by laser welding. See the structural diagram of the composite assembly for details. Figure 1 and Figure 2 shown.
[0075] (2) Connect the first test electrode (busbar) of the prepared composite assembly to the first test end of the charge and discharge test cabinet, and connect the second test electrode (foil) of the composite assembly to the second test end of the charge and discharge test cabinet. The first test end and the first test electrode are bolted together through a round hole with a diameter of 9 mm on the busbar; the second test end is a clamping structure, and the clamp is a low-impedance gold-plated copper material.
[0076] (3) Thermocouples are arranged at the center of gravity of the first welding position, the center of gravity of the second welding position, the center of gravity of the third welding position and the fourth temperature measurement point, respectively. The fourth temperature measurement point is the center of gravity in the plane formed by the first welding position, the second welding position and the third welding position (the middle position of laser welding and ultrasonic welding). The temperature sensing line arrangement points refer to Figure 2As shown, and fix it with high temperature resistant insulating tape.
[0077] (4) The test starting temperature was 25°C, and 696A, 464A, and 232A DC currents were introduced in sequence. The cutoff condition was that the experiment was stopped when any detection position reached 100°C, and the temperature was recorded. The results are shown in Table 1 below.
[0078] Table 1 Experimental results
[0079]
[0080]
[0081]
[0082]
[0083]
[0084]
[0085] After the test, the mechanical stability of the ultrasonic position of the composite component was tested, and the results are shown in Table 2 below.
[0086] Table 2 Mechanical stability test results
[0087]
[0088] By comparing the tensile test results of the ultrasonic connection position before and after the test, it can be found that after the large current is turned on, the tensile test of the ultrasonic weak position has not changed significantly, and the mechanical stability at extreme temperature is good.
[0089] Example 2
[0090] The temperature rise prediction method provided in this embodiment includes the following steps:
[0091] Based on the full factorial design of JMP, the current (I / A), time (t / s), adapter thickness (S1 / mm 2 ) and ultrasonic welding area (S2 / mm 2 ) factors were completely factored out, and the temperature rise was fitted with all effect factors by multiple linear regression. The effect factors were judged and eliminated according to the P value of each factor in the fitting model. Specifically, the effects with a P value greater than 0.05 were considered to have no significant contribution to the model. After removing these effects, the model was refitted to obtain more accurate estimates of the model parameters related to the active effect, so as to achieve the purpose of simplifying the model. The fitting results are shown in Figure 5 As shown in Figure 2, it can be found that the goodness of fit can reach more than 85%, indicating that the model has a good degree of fit.
[0092] The expressions of the prediction models are:
[0093] T 激光位置 =3.9757-0.714×S1+0.1145×I+(S1-30.841)×[(I-405.62)×(-0.004)]+0.3423×t+(S1-30.841)×[(t-74 .238)×(-0.008)]+(I-405.62)×[(t-74.238)×0.0017]+(S1-30.841)×{(I-405.62)×[(t-74.238)×(-5e -5 )]}.
[0094] T 转接片位置 =8.3793-1.883×S1+0.2093×I+(S1-30.841)×[(I-405.62)×(-0.009)]+0.5462×t+(S1-30.841)×[(t-7 4.238)×(-0.018)]+(I-405.62)×[(t-74.238)×0.0029]+(S1-30.841)×{(I-405.62)×[(t-74.238)×(-e -4 )]}.
[0095] T 超声波位置 =18.157-3.376×S1-0.183×S2+0.3344×I+(S1-30.841)×[(I-405.62)×(-0 .018)]+(S2-101.32)×[(I-405.62)×(-0.001)]+0.909×t+(S1-30.841)×[( t-74.238)×(-0.044)]+(S2-101.32)×[(t-74.238)×(-0.002)]+(I-405.6 2)×[(t-74.238)·0.0049]+(S1-30.841)×{(I-405.62)·[(t-74.238)·(-3e -4 )]}+(S2-101.32)×{(I-405.62)·[(t-74.238)·(-e -5 )]}.
[0096] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A method for testing the overcurrent capacity of a lithium battery structural component, characterized in that: The steps include: A composite component is obtained; the composite component comprises a busbar, a top cover plate, an adapter plate and a foil material which are arranged in sequence, wherein one end of the adapter plate is connected to the foil material by ultrasonic welding to form a first welding position and a second welding position, and the foil material is arranged above the adapter plate; a phase change heat transfer material is arranged on the surface of the foil material; the other end of the adapter plate is connected to the pole of the top cover plate by laser welding to form a third welding position, and the top cover plate is arranged below the adapter plate; below the top cover plate, the busbar is connected to the pole of the top cover plate by laser welding; The composite assembly is connected to a charge and discharge test cabinet and a thermocouple respectively, and then a constant current charge or constant current discharge test is performed.
2. The method for testing the current carrying capacity of a lithium battery structural component according to claim 1, characterized in that: At least one of the following conditions is met: (1) The foil material includes aluminum foil or copper foil; (2) The cross-sectional area of the adapter is ≥ 15 mm 2 ; (3) The phase change heat transfer material includes a graphene thermal conductive film.
3. The method for testing the current capacity of a lithium battery structural component according to claim 1, characterized in that: The method for connecting the composite component and the charge and discharge test cabinet includes: using the busbar as a first test electrode and the foil as a second test electrode, connecting the first test electrode and the second test electrode to a first test end and a second test end of the charge and discharge test cabinet respectively; wherein the first test electrode and the first test end are bolted via a through hole on the busbar; the second test end includes a clamping structure, and the second test electrode and the second test end are connected via the clamping structure; the clamping structure includes a low-impedance gold-plated copper material.
4. The method for testing the current carrying capacity of a lithium battery structural component according to claim 1, characterized in that: The method for connecting the composite component and the thermocouple includes: arranging the thermocouple at the first welding position, the second welding position, the third welding position and the fourth temperature measuring point respectively, and fixing them; wherein the fourth temperature measuring point is the center of gravity in the plane formed by the first welding position, the second welding position and the third welding position; the fixing method includes: fixing with high temperature resistant insulating tape.
5. The method for testing the current carrying capacity of a lithium battery structural component according to claim 1, characterized in that: At least one of the following conditions is met: (1) The cut-off condition of the constant current charging or constant current discharging is controlled by temperature rise or power-on time; (2) The test starting temperature of the constant current charge or constant current discharge is 25°C ± 2°C.
6. The method for testing the current capacity of a lithium battery structural component according to claim 1, characterized in that: After the constant current charging or constant current discharging test is completed, a mechanical stability test is performed on the composite component; the mechanical stability test includes a tensile test.
7. A temperature rise prediction method, characterized in that: The method comprises the following steps: performing a complete factorial analysis according to the test results obtained by the test method for the overcurrent capacity of a lithium battery structural component according to any one of claims 1 to 6, establishing a multivariate linear regression fitting model of key factors and temperature rise, and calculating a predicted value of temperature rise.
8. The temperature rise prediction method according to claim 7, characterized in that: The key factors include at least one of current, time, a cross-sectional area of the adapter and an ultrasonic welding area.
9. The temperature rise prediction method according to claim 7, characterized in that: In the process of complete factorial analysis, the P value of each factor in the fitting model is used for judgment and the effect factors with a P value greater than 0.05 are screened out.
10. Use of the method for testing the current carrying capacity of a lithium battery structural component according to any one of claims 1 to 6 or the method for predicting temperature rise according to claim 7 in the preparation of lithium-ion batteries.
